Effect of CO2 on the microstructure and corrosion mechanism of Mg-Nd-Zn-Ca plasma electrolytic oxidation coatings. (March 2023) - Yu, Lang; Jia, Pingping; Zhao, Bocheng; Song, Yunpeng; Wang, Jingtao; Cui, Hongwei; Feng, Rui; Li, Hui; Cui, Xiaoli; Gao, Zengli; Fang, Xiaoying; Zhang, Lijuan; et al.
Abstract: Plasma electrolytic oxide (PEO) coatings have attracted increasing attention as an effective way to protect the substrate and extend the service life of magnesium alloys. Herein, we report a special "additive", i.e., the introduction of CO2 gas in the PEO process, to prepare PEO composite coatings on the surface of Mg-Nd-Zn-Ca alloy. The microscopic morphology, physical phase, and elemental composition of the coating were examined by field emission scanning electron microscopy, transmission electron microscopy, X-ray diffractometer, Fourier infrared spectrometer, and X-ray photoelectron spectrometer. The mechanism of the effect of gas on the corrosion resistance of the coating was investigated by using the electrochemical workstation. The results show that CO2 gas can participate in the formation and growth of the coating through the PEO process, and its introduction is conducive to the formation of Mg(OH)2 on the surface of the coating. In the early stage of the reaction, CO2 produces reactive CO2 * under plasma discharge conditions, which reacts with Mg 2+ to form nanocrystals MgCO3 . While in the late stage of the reaction, the gas blocks the conductive channels, resulting in a blocked ion-to-ion bonding and a slow growth of the coating with a porous appearance, leading to reduced corrosion resistance. Graphical Abstract: ga1